2023
DOI: 10.3389/fpsyt.2023.1121546
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the healthcare workers’ version of the Pandemic Grief Scale among frontline nursing professionals during the COVID-19 pandemic in Korea

Abstract: IntroductionNurses have been repeatedly exposed to unexpected death and grief during COVID-19 pandemic, and it is necessary to provide grief support for the nurses who have experienced the loss of patients to COVID-19. We aimed to explore the reliability and validity of the Pandemic Grief Scale (PGS) for Healthcare Workers among frontline nursing professionals working in COVID-19 inpatient wards whose patients may have died.MethodsAn anonymous online survey was performed among frontline nursing professionals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“… 31 Those with generalized anxiety were found to experience more severe pandemic grief than those without generalized anxiety. 21 In our study, depression and generalized anxiety seem to interfere with the normal grieving process. Given that acute grief response during the initial stages of mourning can elevate the risk of prolonged grief, 8 9 10 it is crucial to address depression and generalized anxiety, particularly among individuals facing higher levels of work-related stress.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“… 31 Those with generalized anxiety were found to experience more severe pandemic grief than those without generalized anxiety. 21 In our study, depression and generalized anxiety seem to interfere with the normal grieving process. Given that acute grief response during the initial stages of mourning can elevate the risk of prolonged grief, 8 9 10 it is crucial to address depression and generalized anxiety, particularly among individuals facing higher levels of work-related stress.…”
Section: Discussionsupporting
confidence: 43%
“… 31 Similarly, another study revealed that pandemic grief is higher in the group of people with depression than those without depression. 21 Besides, generalized anxiety partially mediated the association of work-related stress with pandemic grief. The finding aligns with the previous study’s result, which showed that viral anxiety directly increased pandemic grief.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The PGS scale was also developed to assess healthcare workers’ grief reaction to the COVID-19 pandemic. In this study, we applied the Korean version of PGS validated among healthcare workers [ 31 ] after changing the terms “patient” into “people.” Cronbach’s α among this sample was 0.851.…”
Section: Methodsmentioning
confidence: 99%